Tracheal tumors: Analysis of 35 cases. Clinical description and therapeutic results. - Viola Alles, Alberto; Vasallo, Alberto (Cirugía del Uruguay, 1985)
Study of 35 patients affected by tracheal tumor. Noteworthy in their description is that they are predominan! in the fifth decade, in the lower third of the organ (71.4%); in epidermoid variations (48.6%); in roen (88%) and heavy smokers. Study of 35 patients affected by tracheal tumor. Noteworthy in their description is that they are predominan! in the fifth decade, in the lower third of the organ (71.4%); in epidermoid variations (48.6%); in roen (88%) and heavy smokers.